PERLINDUNGAN HUKUM KORBAN TINDAK PIDANA PENCURIAN RINGAN PADA PROSES DIVERSI TINGKAT PENYIDIKAN - Arfan Kaimuddin (Arena Hukum, 2015)
AbsrtactThis research published as journal is written and motivated by three issues. First is the juridical problems that can be observed from the inconsistency of the Act Number 11 of 2012 on the SPPA from article 1, paragraph (6) of the restorative justice to Article 9 paragraph (2). It has distorted the concept of restorative justice for victims of crime minor theft. The Second is the theoretical issues, that is the right of victims to be protected, but in practice these rights are neglected. the Third issue is the sociological problems that can be observed where the criminal acts of theft committed by a child can interfere with the comfort and safety of the community. This research's objective is to find a basic philosophical formation of Article 9, paragraph (2) of Act No. 11/2012 on SPPA. To describe how should the diversion of the victims of wage theft with losses under local minimum wage was implemented. This journal is written using normative legal research methods. Basic formation of Article 9 (2) Article 9 paragraph (2) of Law No. 11/2012 on SPPA included four main points, three points are meant to protect children in order to avoid prison and then the fourth point is to protect the interests of victims and perpetrators of child. If the victim does not wish to participate, diversion will still run. This philosophical basis is in contrary to the theory of restorative justice and legal protection. In comparison to the Diversion process of Philippines dan Malaysia state, to achieve the ideal form of diversion for criminal offenses minor committed by children in Indonesia is to use a restorative justice approach in a diversion effort. It is supported by the theory of criminal law policy, which is by reformulating and altering the content of Article 9 paragraph (2) of the SPPA. AbsrtakPenulisan jurnal berupa hasil penelitian ini dilatarbelakangi oleh tiga permasalahan. Pertama, permasalahan yuridis yang bisa dicermati dari adanya inkonsistensi dalam UU No. 11 tahun 2012 tentang SPPA yakni antara pasal 1 ayat (6) mengenai restorative justice dengan Pasal 9 ayat (2). Hal ini telah mencederai konsep restorative justice bagi korban tindak pidana pencurian ringan. Kedua, permasalahan teoritis, Hak-hak korban harus dilindungi, namun dalam praktek hak tersebut terabaikan. Ketiga, permasalahan sosiologis yang bisa dicermati ialah Tindak pidana pencurian yang dilakukan oleh anak dapat mengganggu kenyamanan dan keamanan di dalam masyarakat. Tujuan penelitian ini Untuk menemukan dasar filosofis pembentukan Pasal 9 ayat (2) UU No. 11 Tahun 2012 tentang SPPA. Untuk menguraikan bagaimana semestinya proses diversi terhadap korban pencurian yang kerugiannya dibawah upah minum provinsi setempat dilaksanakan. Penulisan jurnal ini menggunakan metode penelitian hukum normatif. Dasar pembentukan Pasal 9 ayat (2) Pasal 9 ayat (2) UU No. 11/2012 tentang SPPAterdapat empat poin utama, tiga poin bertujuan untuk melindungi anak agar terhindar dari penjara kemudian poin keempat yaitu melindungi kepentingan korban dan juga pelaku anak. Apabila korban tidak ingin berpartisipasi, diversi tetap akan dijalankan. Dasar filosofis tersebut bertentangan dengan teori restorative justice dan juga teori perlindungan hukum.Setalah melakukan perbandingan Proses diversi dengan Negara Filiphina dan Malaysia, untuk mencapai bentuk ideal diversi untuk tindak pidana pencurian ringan yang dilakukan oleh anak di Indonesia ialah dengan menggunakan pendekatan restorative justice pada upaya diversi. Hal ini didukungoleh teori kebijakan hukum pidana. Dengan mereformulasi untuk merubah isi dari Pasal 9 ayat (2) UU SPPA.